Aesthetic Reconstruction of Congenital Cerebriform Intradermal Nevus by Sequential Tissue Expansion at an Early Age: Ten-year Follow-up (Annals of Medical Research, 2021)
None
Keywords: Cerebriform Intradermal Nevus; Tissue Expansion; Sequential Tissue Expansion.